Hemodynamic rounds and clinical pathology correlation: Evaluation of a polycythemic patient guided by imaging, hemodynamics, and endomyocardial biopsy - PramodSagar; KothandamSivakumar (Wolters Kluwer Medknow Publications, 2021)
A 32-year-old male with symptomatic polycythemia was investigated by hematologist for myeloproliferative malignancies and underwent five therapeutic phlebotomies. The identification of hypoxia on pulse oximetry later led to pulmonology evaluation that showed normal lung function tests as well as normal lung parenchyma and airways on advanced imaging. The absence of murmurs and significant precordial findings, normal chest X-ray, and unremarkable findings in electrocardiogram apart from first-degree heart block delayed the cardiac referral. Cardiac imaging showed a significant right to left shunt through a large oval fossa defect, mild hypoplasia of the right ventricle, normal right ventricular function and mild fibrosis within the myocardium. Hemodynamic assessment with test balloon occlusion led finally to a complete closure of the defect, which normalized the hypoxia. A step-by-step clinical approach finally leading to the management is presented in this clinicopathology correlation and hemodynamic rounds.